Market Structure and Cost Pass-Through in Retail - Hong, Gee Hee; Li, Nicholas (The Review of Economics and Statistics, 2017)
We examine the extent to which vertical and horizontal market structure can together explain incomplete retail pass-through. To answer this question, we use scanner data from a large U.S. retailer to estimate product level pass-through for three vertical structures: national brands, private label goods not manufactured by the retailer, and private label goods manufactured by the retailer. Our approach circumvents issues associated with internal firm prices and demonstrates that accounting for horizontal market structure is important for measuring the effects of vertical integration and reduced double marginalization on pass-through.